Analysis of Marketing Effect and Individual Modernity Its Influence on Consumption Behavior - Zuhri Saputra Hutabarat; Rosmiati Rosmiati (Universitas Batanghari Jambi, 2022)
This study aims to determine the existence of problems related to the consumptive behavior of students. Because it is known that many students have uncontrolled consumptive behavior in consuming goods and services. This research is a quantitative research using an expo facto research approach. The results showed that: 1) There was a significant marketing effect on consumptive behavior, the value of tcount was 3.936 > ttable 1.65993. 2) There is a significant influence of individual modernity on consumptive behavior, the value of tcount is 6.743 > ttable 1.65993. 3) There is a simultaneous influence of marketing effect and individual modernity on consumptive behavior based on data analysis obtained Fcount 36.819> Ftable 3.09 and coefficient of determination (R Square) of 0.419 which means that consumptive behavior is influenced by marketing effect and individual modernity is 41.9% and the remaining 58.1% is influenced by other variables that are not explained in this study. So it can be concluded that the marketing effect and individual modernity have a positive and significant effect on consumptive behavior in Economic Education students class 2017 and 2018 Jambi University. From the results of this study, it is suggested that students can be wiser in consuming goods and services in excess or consumptive behavior in order to avoid marketing effects and uncontrolled individual modernity.